Вплив фітогенного поля верби козячої (Salix caprea L.) на формування мікроклімату та ріст пагонів - Gorelov, А.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The phytogenic field influence on some parameters of environment and morphogenic indexes in different parts of crown and undercrown space is shown on example Salix caprea L. The peculiarities of their variations and correlations between there are studied. It is established, that some components of phytogenic field have different influence on the shoot growth.